The Greatness of ordinary life biography and teachings of Msgr. Josemaria Escriva (1902-1975). (Makati City Aletheia Foundation and Distributed Processing Systems, 2002)
The greatness of ordinary life multimedia CD-ROm on the life and teachings of Blessed Josemaria Escriva, priest and founder of Opus Dei.
CD-ROM
System requirements for Macintosh: 68040 processor or higher, four-speed CD-ROm drive, 16 megabytes installed RAM, System 7.0 or higher.
System requirements for Windows: 80486 SX 25 Processor or higher, four-speed CD-ROm drive, 256 colores ; recommended: 24-bit true color, 2 megabytes video RAM, 16 megabytes installed RAM, Windows 95, soundblaster or compatible card.
Keywords: Escriva de Balaguer, Jose Maria -- 1902-1975 -- Biography; Opus Dei (Society) -- History